The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2500/ajr.2007.21.3011
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled, Study of Absorbable Nasal Packing on Outcomes of Surgical Treatment of Rhinosinusitis with Polyposis

Abstract: The absorbable dressing showed a trend toward positive effect on early wound healing and in late results. Strong patient preference was indicated for the absorbable dressing over standard sponges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 19 publications
1
89
1
Order By: Relevance
“…There have been two recent randomized studies that have evaluated the effects of absorbable HA nasal packing in patients with rhinosinusitis with or without NP who have undergone sinus surgery. Franklin et al [24] conducted a prospective, randomized, controlled study that investigated the effect of absorbable HA nasal packing on postoperative discomfort and mucosal healing in 35 patients with rhinosinusitis without NP following sinus surgery. Improvements in endoscopic appearances were reported with the absorbable HA nasal packing.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two recent randomized studies that have evaluated the effects of absorbable HA nasal packing in patients with rhinosinusitis with or without NP who have undergone sinus surgery. Franklin et al [24] conducted a prospective, randomized, controlled study that investigated the effect of absorbable HA nasal packing on postoperative discomfort and mucosal healing in 35 patients with rhinosinusitis without NP following sinus surgery. Improvements in endoscopic appearances were reported with the absorbable HA nasal packing.…”
Section: Discussionmentioning
confidence: 99%
“…1293 suggested better early and long-term wound healing for Merogel R , no difference between these agents was observed in 2 other independent RCTs. 1294,1295 Interestingly an RCT by Shi et al 1296 evaluating a similar hyaluronan-based gel, PureRegen Gel R (BioRegen Biomedical, Changzhou, China), observed improved wound healing in terms of adhesion formation, edema, and crusting when the gel was applied to Merocel R prior to packing. This does suggest a possible benefit of hyaluronan gel.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 99%
“…Although when evaluating the efectiveness of any treatment, this is a very important consideration; we believe that it is more important to conclusively determine which means of nasal packing is most clinically efective. We do have to mention that the results from a previous randomized controlled trial, which was not eligible for inclusion in our systematic review/meta-analysis, suggested that the majority of patients prefer absorbable nasal packing material (speciically MeroGel) over nonabsorbable material [10]. Finally four, we only included a relatively small number of studies for our meta-analysis which limited the power of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There were a number of studies comparing the eicacy of nonabsorbable and absorbable nasal packing after FESS [8][9][10][11][12][13][14]; however, the results on if a method is beter than another or if the methods used had a comparable eicacy were conlicting among the studies. In an efort to gain a beter understanding of the eicacy and other outcomes on nonabsorbable vs. absorbable nasal packing after FESS for the treatment of chronic rhinosinusitis, we have conducted a systematic review and a meta-analysis of the available literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation